From Textual to Contextual : A Study of Musdah Mulia's Humanistic Paradigm in Re-Understanding Classical Islamic Literacy - Milda, Muhammad; Irsyadiah, Afifah Kurnia; Ramadhiah, Syafitri; Azzahra, Desfa Rizqi; Amelia, Diana Sarah; Khuluqi, Hazfil Alif Hassin; Prasetyo, Muhammad Agung (International Tatho Academics, 2025)
The study aims to analyze Musdah Mulia's humanist approach through a contextual and interdisciplinary interpretation of Islamic texts, integrating feminist, pedagogical, and Islamic reformist perspectives. The research employs a qualitative method with a textual-contextual approach, using primary data from Musdah Mulia's writings and supported by Abdurrahman Wahid’s theory of Islamic humanism. Analysis focuses on five basic rights within the framework of maqashid al-syari’ah. The findings show that Musdah Mulia emphasizes contextualish that prioritizes human dignity, social justice, and gender equality. Her thought challenges patriarchal religious interpretations and promotes an inclusive, progressive Islamic discourse. Theoretically, this study strengthens the paradigm of progressive Islam that places human values as central to religious understanding.